65.6k views
1 vote
4(3x - 2) - x = 3x - 4x

User Marklam
by
5.3k points

2 Answers

0 votes

Answer:


\displaystyle{x=(2)/(3)}

Explanation:


4(3x-2)-x=3x-4x\\(12x-8)-x=3x-4x\\12x-x-8=3x-4x\\11x-8=3x-4x\\11x-8=-x\\11x=-x+8\\12x=8


\displaystyle{x=(8)/(12)}


\displaystyle{x=(2)/(3)}

User Kyre
by
5.0k points
6 votes

Answer:

2/3

Explanation:

Step 1:

4 ( 3x - 2 ) - x = 3x - 4x

Step 2:

12x - 8 - x = - x

Step 3:

11x - 8 = - x

Step 4:

11x = - x + 8

Step 5:

12x = 8

Answer:

x = 2/3

Hope This Helps :)

User Brave
by
5.4k points